Dealing with Juvenile Delinquency: Integrated Social Work Approach - Paramjit Singh Jamir Singh; Azlinda Azman (Asian Social Work Journal, 2020)
Juvenile delinquency poses a constant social challenge to the public. Juvenile delinquency can be defined as a repeated social disorder among children or adolescents. In this regard, human behaviour and the environment are linked to each other. Hence, the distortion of one aspect will definitely affect the latter. This article presents a comprehensive intervention where the integrated social work approach was applied to deal with juvenile delinquency. The integrated social work approach has become a framework for social work as it focuses on both the individuals and the environment. This framework has been applied to reduce the gap between individuals and their environments, and it is very important for social work intervention. Since the nature of this framework encompasses several different professions, it has become beneficial for social workers to deliver a multi-context intervention and assessment that is based on the preventive, rehabilitative, and development perspectives, especially in the case of juvenile delinquency. The implementation of an integrated social work framework in the line of a social worker’s profession could bring advantages in terms of pinpointing the cause of the problems. Finally, social workers will be able to address juvenile delinquency problems through appropriate techniques.